NEAR at n_TOF/CERN: Preparing the first multi-foil activation measurement - Goula, Styliani; Patronis, Nikolas; Stamati, Maria-Elisso; Chasapoglou, Sotirios; Diakaki, Maria; Colonna, Nicola; Eleme, Zinovia; Georgali, Efstathia; Kokkoris, Michael; Mengoni, Alberto; Michalopoulou, Veatriki; Peoviti, Maria; et al. (HNPS Advances in Nuclear Physics, 2022)
The n_TOF facility at CERN is a neutron Time-Of-Flight facility based on a spallation neutron source. During the Second Long Shutdown (LS2) , a new experimental zone was designed and delivered. This new experimental area -the NEAR station - is located very close to the lead spallation target, at a distance of just 3m. In this way, the high luminosity of the n_TOF neutron spallation source can be fully exploited. Towards the characterization of the new experimental area as well for the benchmarking of the performed simulations, the multi-foil activation measurement will be implemented. Eleven threshold and seven capture reference reactions will be utilized for the unfolding of the NEAR neutron beam energy spectrum that stretches from the meV to the GeV region.